Repulsive axon guidance: abelson and enabled play opposing roles downstream of the roundabout receptor. - Bashaw, G.J.; Kidd, T.; Murray, D.; Pawson, T.; Goodman, C.S. (Cell, 2000)
Drosophila Roundabout (Robo) is the founding member of a conserved family of repulsive axon guidance receptors that respond to secreted Slit proteins. Little is known about the signaling mechanisms which function downstream of Robo to mediate repulsion. Here, we present genetic and biochemical evidence that the Abelson (Abl) tyrosine kinase and its substrate Enabled (Ena) play direct and opposing roles in Robo signal transduction. Genetic interactions support a model in which Abl functions to antagonize Robo signaling, while Ena is required in part for Robo's repulsive output. Both Abl and Ena can directly bind to Robo's cytoplasmic domain. A mutant form of Robo that interferes with Ena binding is partially impaired in Robo function, while a mutation in a conserved cytoplasmic tyrosine that can be phosphorylated by Abl generates a hyperactive Robo receptor.